Microwear analysis aiding excavation prioritization at the submerged Mesolithic settlement of Orehoved, Denmark. (February 2019) - Donahue, Randolph E.; Fischer, Anders; Burroni, Daniela B.; Malm, Torben; Johansen, Morten
Abstract: Microwear analysis of lithic debris offers an aid to field archaeologists in need of focusing excavation activity at the parts of Stone Age sites that are least disturbed by post-depositional processes. In this progress report we describe the ridge-wear approach and report on its application to the submerged Mesolithic settlement of Orehoved, Denmark. Test-pitting had provided worked flints from two distinctive layers within an area of ca. 2.8 ha, located 4–7 m below present sea level. Through analysis of wear on dorsal ridges on flint flakes we demonstrate that the assemblages of artefacts from both strata spanned the whole range from minimally-rounded to extremely-rounded. Spatial and statistical analyses indicate that both layers contain redeposited artefacts . Major parts of higher ground areas were therefore considered so disturbed by sea-level rise that further excavation should be avoided here . Follow-up excavation in a more low lying area located a third and stratigraphically deeper layer with numerous artefacts in stone, bone, and plant material in situ .